The Impact Of Selected Components Of Public Expenditure And Economic Growth In Sri Lanka During 1990-2022: An Econometric Analysis - Jathushanthini, V.; Vijayakumar, S. (Journal of Business Economics, 2024)
Purpose: Public expenditure is one of the most important instrument of fiscal policy. It is most affect the economic growth. So this study examined the impact of selected components of public expenditure and economic growth in sri Lanka during the period of 1990-2022 and find out the long run and short run relationship between selected components of public expenditure and economic growth in sri Lanka. Selected components of public expenditure are such as defence, health, transport and communication and interest payments. Methodology: This study is entirely quantitative analysis which is based on secondary time series data. For the study have obtained from the annual report of central Bank of Sri Lanka (CBSL) Department Of census and statistics website and world development indicators website. Economic growth is used as a dependent variable and defence, health, transport and communication and interest payment have been used as independent variables. Dependent and independent variables are used as a percentage of GDP. The independent variables have been converted into Logarithms to avoid the heteroscedasticity problem among the variables. Many econometric tools such as ADF unit root test, Diagnostic test, ARDL model, ARDL Bound test and Error correction model test have been employed to analyse the data. Findings: This study found that defence and interest payment have a negative impact on economic growth. And health, transport and communication have a positive impact on economic growth. More fund are allocated to defence and interest payments, those are negative impact on economic growth, In is greater than Health and transport and communication expenditure. Implications: Therefore, the government should allocate the required more funds to the components of public expenditure which induce the economic development. Theoretical Contribution: Assessing the effectiveness of various more funds to the components of public expenditure which induce the economic development. Originality: Employing novel data analysis, techniques or econometric models to study the relationship between public expenditure components and economic growth can offer fresh insights.
Keywords: Public expenditure; Economic growth; Econometric analysis; ARDL model